MENAKAR JALUR PENDIDIKAN LUAR SEKOLAH: MEMUNCULKAN ASA DI ERA OTONOMI DAERAH - Ulum, M Miftahul (Cendekia: Jurnal Kependidikan Dan Kemasyarakatan, 2011)
Low Human Resources we are not separated from the low level of public education, especially at school age. The low quality of human resources is caused by many things, such as the inability of school-age children to continue their education to higher education, as a result of poverty is wrapped around family life, or could have been caused by the dropout rate, the same is caused by economic factors. Therefore, an optimistic attitude necessary to be able to raise these human resources. One of the pillars which can not be overlooked is through non-formal education, or better known outside of school education (PLS). Government through the spirit of regional autonomy shall move the non-formal educational programs such as Law No. 20 on National Education System candidly and explicitly states that non-formal education will continue to be cultivated within the framework to create community-based education, and government share responsibility sustainability of non-formal education as an effort to complete the 9-year compulsory education.Â ÙÙØ§ ÙÙØµÙ Ø¨ÙÙ Ø§ÙÙÙØ§Ø±Ø¯ Ø§ÙØ¨Ø´Ø±ÙØ© Ø§ÙÙÙØ®ÙØ¶Ø© ÙØÙ ÙÙ ØªØ¯ÙÙ ÙØ³ØªÙÙ Ø§ÙØªØ¹ÙÙÙ Ø§ÙØ¹Ø§ÙØ ÙØ®Ø§ØµØ© ÙÙ Ø³Ù Ø§ÙÙØ¯Ø±Ø³Ø©. ÙÙØªØ³Ø¨Ø¨ Ø§ÙØ®ÙØ§Ø¶ Ø¬ÙØ¯Ø© Ø§ÙÙÙØ§Ø±Ø¯ Ø§ÙØ¨Ø´Ø±ÙØ© ÙÙ Ø®ÙØ§Ù Ø§ÙØ¹Ø¯ÙØ¯ ÙÙ Ø§ÙØ£Ø´ÙØ§Ø¡Ø ÙØ«Ù Ø¹Ø¯Ù ÙØ¯Ø±Ø© Ø§ÙØ£Ø·ÙØ§Ù ÙÙ Ø³Ù Ø§ÙÙØ¯Ø±Ø³Ø© ÙÙÙØ§ØµÙØ© ØªØ¹ÙÙÙÙÙ ÙÙ Ø§ÙØªØ¹ÙÙÙ Ø§ÙØ¹Ø§ÙÙØ ÙØªÙØ¬Ø© ÙØ§ÙØªÙØ§Ù Ø§ÙÙÙØ± ØÙÙ ØÙØ§Ø© Ø§ÙØ£Ø³Ø±Ø© Ø Ø£Ù ÙÙÙÙ Ø£Ù ÙÙÙÙ ÙØ§Ø¬ÙØ§ Ø¹Ù ÙØ¹Ø¯Ù Ø§ÙØªØ³Ø±Ø¨ ÙÙ Ø§ÙÙØ¯Ø§Ø±Ø³Ø ÙÙØªØ³Ø¨Ø¨ ÙÙ ÙÙØ³ Ø§ÙØ¹ÙØ§ÙÙ Ø§ÙØ§ÙØªØµØ§Ø¯ÙØ©. ÙÙØ°ÙÙØ ÙÙØ°Ø§ ÙÙÙÙ ÙØªÙØ§Ø¦Ù Ø§ÙÙØ§Ø²ÙØ© ÙØªÙÙÙ ÙØ§Ø¯Ø±Ø© Ø¹ÙÙ Ø±ÙØ¹ ÙØ°Ù Ø§ÙÙÙØ§Ø±Ø¯ Ø§ÙØ¨Ø´Ø±ÙØ©. ÙØ§ØØ¯Ø© ÙÙ Ø§ÙØ±ÙØ§Ø¦Ø² Ø§ÙØªÙ ÙØ§ ÙÙÙÙ ØªØ¬Ø§ÙÙÙØ§ ÙÙ ÙÙ Ø®ÙØ§Ù Ø§ÙØªØ¹ÙÙÙ ØºÙØ± Ø§ÙÙØ¸Ø§ÙÙØ Ø£Ù Ø§ÙÙØ¹Ø±ÙÙ Ø®Ø§Ø±Ø¬ Ø§ÙÙØ¯Ø±Ø³Ø© ÙØ§ÙØªØ¹ÙÙÙ (PLS). ÙØ§ÙØÙÙÙØ© ÙÙ Ø®ÙØ§Ù Ø±ÙØ Ø§ÙØÙÙ Ø§ÙØ°Ø§ØªÙ Ø§ÙØ§ÙÙÙÙÙ ÙÙÙ Ø§ÙØ¨Ø±Ø§ÙØ¬ ØºÙØ± Ø±Ø³ÙÙØ© Ø§ÙØªØ¹ÙÙÙÙØ© ÙØ«Ù Ø§ÙÙØ§ÙÙÙ Ø±ÙÙ 20 Ø¨Ø´Ø£Ù ÙØ¸Ø§Ù Ø§ÙØªØ¹ÙÙÙ Ø§ÙÙØ·ÙÙ Ø¨ØµØ±Ø§ØØ© ÙØªÙØµ ØµØ±Ø§ØØ© Ø¹ÙÙ Ø£Ù Ø§ÙØªØ¹ÙÙÙ ØºÙØ± Ø§ÙÙØ¸Ø§ÙÙ ÙØ³ØªÙØ± ÙØ²Ø±Ø§Ø¹ØªÙØ§ ÙÙ Ø¥Ø·Ø§Ø± ÙØ®ÙÙ Ø§ÙÙØ¬ØªÙØ¹ Ø§ÙÙØ§Ø¦Ù Ø¹ÙÙ Ø§ÙØªØ¹ÙÙÙ Ø ÙØ§ÙØ§Ø³ØªØ¯Ø§ÙØ© Ø§ÙØÙÙÙØ© ÙØ³Ø¤ÙÙÙØ© ØØµØ© Ø§ÙØªØ¹ÙÙÙ ØºÙØ± Ø§ÙÙØ¸Ø§ÙÙ ÙÙ ÙØ³Ø¹Ù ÙØ¥ÙÙØ§Ù Ø§ÙØªØ¹ÙÙÙ Ø§ÙØ¥ÙØ²Ø§ÙÙ 9 Ø³ÙÙØ§Øª